2015
DOI: 10.1167/iovs.15-17284
|View full text |Cite
|
Sign up to set email alerts
|

Focused Tortuosity Definitions Based on Expert Clinical Assessment of Corneal Subbasal Nerves

Abstract: Definitions of tortuosity specifying short or long-range tortuosity and considering only the most tortuous nerve in an image improved the agreement in tortuosity grading among a group of expert observers. These definitions could improve accuracy and consistency in quantifying subbasal nerve tortuosity in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…71 Tortuosity is becoming extensively used as a feature to describe subbasal nerves in healthy and pathological corneas. 139 Lagali et al performed an interesting study, focusing on the perception of experts and definitions of tortuosity, and concluded that reproducibility in tortuosity analysis can be subject to sampling bias regardless of the definition used and that further efforts are required to develop standardized quantification strategies. 139 …”
Section: Corneal Nerves In Normal Subjects With and Without Contacmentioning
confidence: 99%
“…71 Tortuosity is becoming extensively used as a feature to describe subbasal nerves in healthy and pathological corneas. 139 Lagali et al performed an interesting study, focusing on the perception of experts and definitions of tortuosity, and concluded that reproducibility in tortuosity analysis can be subject to sampling bias regardless of the definition used and that further efforts are required to develop standardized quantification strategies. 139 …”
Section: Corneal Nerves In Normal Subjects With and Without Contacmentioning
confidence: 99%
“…Previous studies used manual and automated tracing to define the tortuosity mostly on the basis of the individual standard. 22, 24, 27, 30, 31, 3638 We used a different grading scale (Figure 1) because of the different presentation and severe nerve drop out in LSCD. The degrees of tortuosity of the nerve differed significantly among the early, intermediate, and late stages of LSCD and increased in the more severe stages.…”
Section: Discussionmentioning
confidence: 99%
“…In normal corneas, sensory nerve regeneration is robust, starting near the limbus with newly formed sensory nerve fibers and endings arranged in parallel and extending radially toward the center of the cornea (16,18,19). Diabetic mouse corneas exhibit changes similar to those observed in diabetic human corneas, with fewer nerve insertion sites near the limbus, and severely delayed regeneration of sensory nerve endings that exhibit a tortuous, fragmented appearance (20). Neurotrophins expressed by the developing cornea, including nerve growth factor, brain-derived neurotrophic factor, ciliary neurotrophic factor, and neurotrophin-3, have been shown to play a critical role in attracting sensory nerves (21).…”
mentioning
confidence: 88%